Pengaplikasian Planter Bench Sebagai Sarana Duduk pada Restoran dengan Pendekatan Biophilic - Annauval, Alfin Izzah; Firdaus, Boyke Arief Taufik (Fakultas Desain Universitas Komputer Indonesia, 2024)
Restaurants are public facilities that can be found in several places including campus areas. The phenomenon of urban society is the habit of instant life that has the potential to increase stress but it is not matched by activities to achieve balance. Public facilities such as restaurants can contribute to providing such balance through the selection of appropriate design styles and approaches. The combination of contemporary style with the biophilia approach as a form of human affiliation with nature is the answer to the needs of urban people who crave harmony in life. The more advanced an era is, it is directly proportional to the development of furniture design as one of the interior elements. Multifunctional furniture now dominates the market with the presence of new problems in an increasingly modern world. One of them is the planter bench, which is furniture that can accommodate sitting needs and give a touch of nature both through shape, material, and supporting elements such as. This furniture combines the function of sitting and the need for green space on limited land. The addition of plants can benefit both physically and psychologically the user